Development of a French‐language early literacy scale: structural analysis and links between the dimensions of early literacy. (10th January 2021) - Thomas, Aude; Tazouti, Youssef; Hoareau, Lara; Luxembourger, Christophe; Hubert, Blandine; Fischer, Jean‐Paul; Jarlégan, Annette
Abstract : Background: The development of early literacy skills in preschoolers is an important predictor of future academic performance. Four main domains of early literacy are currently observed: letter knowledge, vocabulary, phonological awareness and oral comprehension. A multiplicity of tasks or tests measures these domains in English language. However, there are currently no French‐language tools for evaluating and monitoring the early literacy abilities of young children in francophone contexts. Methods: This paper addresses this lack by presenting a new French‐language scale – the Echelle Préscolaire de Littératie Emergente (EPLE) – for assessing the early literacy skills of preschoolers. In addition to examining the EPLE's psychometric properties, we used path analysis to determine possible links between different dimensions of early literacy and children's characteristics (sex, age and socioeconomic status). Results: This study involves 167 French preschoolers (mean = 5.17 years, standard deviation = 0.59) attending kindergarten. All the participants were tested individually, and a specific entry in the tasks was proposed depending on the age of the children. First, the EPLE had good psychometric properties. Then, factor analysis of the data collected revealed a similar hierarchical factor structure as found in the literature. In addition, we found links between the four dimensions of early literacy measured by the EPLE and both children's age and socioeconomic status. Conclusion: The EPLE creates several new opportunities for early literacy research in French‐speaking contexts. First, this tool reduces the gap in the field of testing young children skills. Then, it allows the comparison with worldwide researches. Moreover, this tool proposes pedagogical implications. In the next few years, the EPLE will be used by teachers or school psychologists to test the early competences of French children.